Challenges of Educational Institutions during the Covid-19 Pandemic - Wayan Ariastana; I Wayan Putra Yasa; I Made Arya Suta Wirawan (Universitas Pendidikan Ganesha, 2022)
The background for the formation of PKBM Lestari was the result of adopting children who dropped out of school in Sumberkima Village and its surroundings. The purpose of the study was to find out the learning process of PKBM Lestari in Sumberkima Village during the Covid-19 Pandemic along with the obstacles experienced in the learning process and efforts to overcome the obstacles experienced in the learning process. This study uses a descriptive qualitative method with the object of research being PKBM Lestari learning during the Covid-19 pandemic by using interviews, observation, and documentation studies. PKBM Lestari follows the letter the circular by implementing an online learning system. In its application there are several obstacles experienced including students who do not have mobile phones, constrained internet data quotas, students who are already working, and lack of mastery in using technology. Based on these obstacles, the solutions offered include submitting internet data quotas, group study, the Equality Education Exam carried out face-to-face, as well as taking and collecting assignments directly to the PKBM Office.